MANIPULASI BUDAYA DALAM POLITIK PADA PEMEKARAN DAERAH - Yulianus Pongtuluran; Ichlasul Amal; Erwan Agus Purwanto (Jurnal Ilmiah Mimbar Demokrasi, 2012)
This research about cultural manipulation in local politic, Toraja, South Sulawesi. The purpose of this study was to determine the local cultural forms are manipulated by local political elites to achieve their political objectives. The methodology used in this study is descriptive qualitative, with the determination of key informants through snowball sampling. The research results showed there has been manipulation of culture by utilizing culture (traditional parties, burial ceremonies, traditional houses, houses of worship, and cultural symbols) as a political instrument to achieve political goals and is used as one reasons in regional expansion.